An economic evaluation of phacoemulsification and extracapsular cataract extraction in cataract surgery - Radujević, Katarina; Bogavac Stanojević, Nataša; Nedeljković, Rade; Lakić, Dragana (Vojnosanitetski pregled, 2023)
Background/Aim. Cataract surgery is one of the most often performed surgical interventions. The predominant method in Western countries is phacoemulsification, while in developing countries, the extracapsular cataract extraction (ECCE) method remains popular. The aim of the study was to evaluate the cost-effectiveness of these two cataract surgery techniques from the provider’s perspective if operation complications were the outcome of the interest. Methods. The data were obtained from the Department of Ophthalmology of the General Hospital Kruševac during a one-year period. A total of 1,179 surgeries by five surgeons were performed. The cost-effectiveness was evaluated using the decision tree. All probabilities were calculated based on the likelihood of the occurrence during the study period. Only direct costs were considered, and values were taken from the documentation at the hospital and the official price list of health services. One- and two-way sensitivity analyses were performed. Results. The total cost per patient in the phacoemulsification group was 71,008.70 Serbian dinars (RSD), while the total cost in the ECCE group was 74,340.36 RSD. At the same time, phacoemulsification shows higher effectiveness than the ECCE method, with 87% and 57% of patients without complications, respectively. With these results, phacoemulsification was the dominant strategy compared to ECCE. The sensitivity analysis revealed that the results are sensitive to the number of performed operations per year. Conclusion. The phacoemulsification technique seems to be the preferred technique for cataract surgery. All the investment in phacoemulsification equipment and consumables is justified if the number of surgeries per year exceeds 350.